eCM 2011
DOI: 10.22203/ecm.v021a39
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus pulposus cell-matrix interactions with laminins

Abstract: The cells of the nucleus pulposus (NP) region of the intervertebral disc play a critical role in this tissue's generation and maintenance, and alterations in NP cell viability, metabolism, and phenotype with aging may be key contributors to progressive disc degeneration. Relatively little is understood about the phenotype of NP cells, including their cell-matrix interactions which may modulate phenotype and survival. Our previous work has identifi ed strong and region-specifi c expression of laminins and lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 60 publications
5
66
0
Order By: Relevance
“…For this to be possible, a comprehensive phenotypic characterization of notochordal cells, and especially of markers specific to the notochordal cells in the human IVD would be required. To date, several attempts have been made to identify notochordal markers, either by comparing the gene expression of immature notochordal rat NP with its costal cartilage [73], rat NP tissue with different degrees of maturity [74][75][76], comparing immature pig NP with AF cells [74,77], sorted large and granular with smaller, less granular pig NP cells [78], immature human NP with AF cells [74] or NP from human juvenile scoliotic and adult discs [79] (Tables 1, 2, 3, 4 list putative notochordal/ immature NP markers identified in different species and describe their relevance to the IVD field). Proposed rat notochordal markers identified in these studies were CD55 [73], brachyury, neuropilin (Nrp-1), CD221, BASP-1 [76], N-Cad [73,76], TGF-b, BMP-6 and CTGF [75].…”
Section: T (Brachyury) Ratmentioning
confidence: 99%
See 2 more Smart Citations
“…For this to be possible, a comprehensive phenotypic characterization of notochordal cells, and especially of markers specific to the notochordal cells in the human IVD would be required. To date, several attempts have been made to identify notochordal markers, either by comparing the gene expression of immature notochordal rat NP with its costal cartilage [73], rat NP tissue with different degrees of maturity [74][75][76], comparing immature pig NP with AF cells [74,77], sorted large and granular with smaller, less granular pig NP cells [78], immature human NP with AF cells [74] or NP from human juvenile scoliotic and adult discs [79] (Tables 1, 2, 3, 4 list putative notochordal/ immature NP markers identified in different species and describe their relevance to the IVD field). Proposed rat notochordal markers identified in these studies were CD55 [73], brachyury, neuropilin (Nrp-1), CD221, BASP-1 [76], N-Cad [73,76], TGF-b, BMP-6 and CTGF [75].…”
Section: T (Brachyury) Ratmentioning
confidence: 99%
“…Integrins and CD239 are expressed by NP cells and are responsible for their adhesion to laminins [74,77] Integrin subunits a3, a6 and ß4)…”
Section: Porcinementioning
confidence: 99%
See 1 more Smart Citation
“…5,6,9 This work relied on enzymatic digestion protocols and plating on laminin-rich substrates to retain physaliphorous cells from the parent tumor that retain the CD24+ and T+ molecular profile of the parent tumor in cell culture and in xenografts generated in NOD/SCID/IL2Rγ null mice. Studies of isolated cells in culture and xenografts derived from these cells were compared with the U-CH1 and U-CH2b cell lines.…”
mentioning
confidence: 99%
“…In NPCs, a higher expression of the laminin a5 chain, laminin receptor integrin subunits a3, a6, and b4 along with CD239 and CD151 were found compared to cells from the AF [85]. Gilchrist et al also examined the cell-matrix interactions and found a faster cell spreading and a higher resistance to detachment on laminin isoforms LM-511 and LM-332, in contrast to LM-111, fibronectin, and collagen II [86]. Substrates coated with laminin softer than 720 Pa were also found to promote in vitro PG production [87].…”
Section: Integrin-mediated Interactions Between Npcs and Ecmmentioning
confidence: 99%